1990
DOI: 10.1136/ard.49.12.994
|View full text |Cite
|
Sign up to set email alerts
|

Brucella arthritis: a study of 96 cases in Kuwait.

Abstract: Of 400 patients with bruceilosis, 104 (26%) had arthritis, of whom 96 could be followed up. The systemic disease in the 96 patients was acute in 54 (56%), subacute in 24 (25%), and chronic in 18 (19%). The main presenting symptoms were joint pain, fever, sweating, and easy fatigability. The joints most commonly affected were the sacroiliac joint (26%) and knee (25%) followed by hip (18%) and spine (8%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
85
2
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 23 publications
7
85
2
2
Order By: Relevance
“…Treatment with a combination of streptomycin plus tetracyclines or rifampicin results in rapid cure rate and resolution of arthritis without sequelae [4]. In subacute cases, pain in the hip joint may sometimes only be elicited by the Gaenslen and FABERE (Flexion, Abduction, External rotation and Extension) manouvre [2]. In the case presented, the diagnosis would have been overlooked had the treating physician not been aware of tbis entity.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Treatment with a combination of streptomycin plus tetracyclines or rifampicin results in rapid cure rate and resolution of arthritis without sequelae [4]. In subacute cases, pain in the hip joint may sometimes only be elicited by the Gaenslen and FABERE (Flexion, Abduction, External rotation and Extension) manouvre [2]. In the case presented, the diagnosis would have been overlooked had the treating physician not been aware of tbis entity.…”
Section: Discussionmentioning
confidence: 86%
“…In a series of 400 patients in Kuwait, 26% had some form of arthritis [2]. The joints most commonly involved are the sacroiliac joint and knee followed by the hip and spine.…”
Section: Discussionmentioning
confidence: 99%
“…4 Though there are numerous reports about hip and knee involvement of the disease, involvement of the elbow is very rarely encountered. 1,2,5 In some Gürsu ve ark. Ortopedi ve Travmatoloji sporadic studies olecranon bursitis have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In the literature, there are numerous reports about patients with brucellosis of the spine, hip and the knee. 1,2,5 In this study, we are presenting a case with brucellar arthritis of the elbow and thus discuss the conBrucellar Arthritis of the Elbow:…”
mentioning
confidence: 99%
“…It is a systemic disease in which every organ can be affected [1]. Osteoarticular complications are common (up to 10%-85% of all cases) and can manifest as sacroiliitis, arthritis, spondylitis, osteomyelitis, tenosynovitis and borsitis [6][7][8].…”
Section: Discussionmentioning
confidence: 99%